Ambliopia : Prevalensi, Faktor Resiko, Klasifikasi, dan Terapi: Prevalensi, Faktor Resiko, Klasifikasi, dan Terapi - Muthia Aya Syahmalya (Yayasan Pendidikan Medika Indonesia, 2022)
Amblyopia or visual impairment which is often known as “lazy eye” is caused by the failure of cortical visual development in one or both eyes caused by ocular pathology in early life. According to available data, nearly 3% of the world's population has amblyopia and 1.2% is at risk of lifelong vision loss. Amblyopia is expected to increase by 4 times by 2040. Most cases can be prevented if detected early. This study was conducted to see how big the prevalence of amblyopia is and to analyze what factors can influence the incidence of amblyopia, as well as to discuss classification and therapy which of course are growing every year. This study uses inclusion criteria in the form of literature published since 2013 and exclusion criteria in the form of literature uploaded before 2013 or 2012 and below. The results of this study showed that the prevalence of patients with amblyopia was quite high with the main characteristics occurring in children. Risk factors that predispose to premature birth, developmental errors of the visual eye system, refractive errors, and family history. Amblyopia can be classified according to cause into strabismic amblyopia, refractive amblyopia, anisoametropic amblyopia, and deprivation amblyopia. Amblyopia therapy should be done early, even the ideal age is done under 7 years so as not to aggravate amblyopia. The therapy that can be given is in the form of correction of refractive errors, occlusion therapy, and pharmacological therapy.